The impact of exchange rate volatility on manufacturing sector in sub-Saharan Africa (1980-2015) - Taiwo Akinlo (Jurnal Perspektif Pembiayaan dan Pembangunan Daerah, 2018)
This study examined the impact of exchange rate volatility on manufacturing sectors in selected sub-Saharan Africa from the period 1980 to 2015. Panel data regression analysis was adopted in the study. Panel pooled OLS, panel fixed effect and Dynamic Generalised Method of Moment models were used for the estimation. The pooled OLS result shows that Gross Domestic Products and physical capital have positive impact on economic growth in sub-Saharan Africa while trade openness, interest rates and exchange rate volatility have negative impact on manufacturing sector. The results from fixed effect and Dynamic Method of moment model shows that trade openness, interest rate and exchange rate volatility have negative impact on manufacturing sector.